Non-contact tonometry: predicting intraocular pressure using a material—corneal thickness—independent methodology - Redaelli, Elena; Calvo, Begoña; Rodriguez Matas, Jose Felix; Luraghi, Giulia; Grasa, Jorge (Frontiers in Bioengineering and Biotechnology, 2024)
Glaucoma, a leading cause of blindness worldwide, is primarily caused by elevated intraocular pressure (IOP). Accurate and reliable IOP measurements are the key to diagnose the pathology in time and to provide for effective treatment strategies. The currently available methods for measuring IOP include contact and non-contact tonometers (NCT), which estimate IOP based on the corneal deformation caused by an external load, that in the case of NCT is an air pulse. The deformation of the cornea during the tonometry is the result of the coupling between the IOP, the mechanical properties of the corneal tissue, the corneal thickness, and the external force applied.Therefore, there is the need to decouple the four contributions to estimate the IOP more reliably. This paper aims to propose a new methodology to estimate the IOP based on the analysis of the mechanical work performed by the air jet and by the IOP during the NCT test. A numerical eye model is presented, initially deformed by the action of a falling mass to study the energy balance. Subsequently, Fluid-Structure Interaction (FSI) simulations are conducted to simulate the action of Corvis ST. The new IOP estimation procedure is proposed based on the results of the simulations. The methodology is centred on the analysis of the time of maximum apex velocity rather than the point of first applanation leading to a new IOP estimation not influenced by the geometrical and mechanical corneal factors.